Diversity of endophytic fungi from Vernonia amygdalina, their phenolic and flavonoid contents and bioactivities - Praptiwi Praptiwi; Ahmad Fathoni; Muhammad Ilyas (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Praptiwi, Fathoni A, Ilyas M. 2019. Diversity of endophytic fungi from Vernonia amygdalina, their phenolic and flavonoid contents and bioactivities. Biodiversitas 20: 436-441. There are nine endophytic fungi in total associated with stem and leaves of Vernonia amygdalina were determined for their total phenolic and flavonoids content as well as assessed for their antibacterial and antioxidant activities. Total phenolic and flavonoid contents were determined by spectrophotometric methods. The antibacterial activity was performed using Thin Layer Chromatography (TLC) - Bioautography assay against S.aureus and E.coli. The antioxidant activity was carried out using TLC- Bioautography by DPPH scavenging assay. Broth serial microdilution assay was used to determine the minimum inhibitory concentrations (MIC) and the half-maximum inhibitory concentration (IC50). Among the identified isolates, there was one isolate of Phomopsis sp., two isolates of Phoma sp., two isolates of Lasiodiplodia sp., two isolates of Colletotrichum sp. and two isolates of Phyllosticta sp. The results showed that the phenolic contents were ranging from 0.53-116.03 mg GAE/g extract, flavonoids contents were ranging from 81.12 to 390.21 mg quercetin equivalent (QE)/g extract. MICs of endophytic fungi against S.aureus and E.coli ranged from 256 to >256 µg/mL and >256 µg/mL respectively that categorized as moderate antibacterial activity. The antioxidant activity of endophytic fungi associated with V. amygdalina was >128 µg/mL, and the antioxidant activity index (AAI) was 0.24.